DESIGNING ANIMATED VIDEO AS SUPPLEMENTARY MATERIALS OF SIMPLE PAST TENSE IN WRITING RECOUNT TEXT - Hartati, Eriani; Salam, Urai; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to design ANEMO; an animated explainer video as the supplementary materials of simple past tense in writing recount text. This developmental research was conducted to find out the performance gap in the learning process caused by the probability of the insufficient materials in the teaching sources. There were four phases of ADDIE instructional design applied namely Analyzing, Designing, Developing, and Evaluation. The ANEMO was created for about 20 minutes for the teaching material (introduction to recount text and simple past tense) and 15 minutes more for the simple past tense exercises. The animated video was completed by voice over and appropriate learning materials, so that, the learners would only need to watch, listen and follow the learning instructions. Last, the product was assessed by two validators according to 20 evaluation statements asking about three aspects of content appropriateness, instructional design, and the technical design of the product. The total score of the assessment rubric was 95% and 93.75% which categorized as very good. In sum, the product has been well-developed and has met both the teacher and students? need as supplementary materials to support the teaching of simple past tense in writing recount text. Keywords: Animated Video, Supplementary, Simple Past Tense, Recount Text.